2016
DOI: 10.1007/s12053-016-9478-z
|View full text |Cite
|
Sign up to set email alerts
|

Toward greener supply chains: is there a role for the new ISO 50001 approach to energy and carbon management?

Abstract: Considering the increased interest of stakeholders in climate change and a low-carbon economy, this article has investigated and identified several contributions of the ISO 50001 in support of the adoption of green supply chain management (GSCM). In this context, energy efficiency and reduced CO 2 emissions are critical. Therefore, the proposal for and the requirements of ISO 50001 can generate useful insights on how to structure green and low-carbon supply chains, hence helping to address the challenges posed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 50 publications
1
27
0
Order By: Relevance
“…To increase their market share, suppliers are actively implementing environmental initiatives as a response to the demands from the retailer [41]. Environmental demands on suppliers have been raised by other authors as well, e.g., References [8,10,13,18,24,42,43]. The evaluation and auditing of suppliers, as well as visiting suppliers' sites, are important parts of a green purchasing strategy [8,10,18].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To increase their market share, suppliers are actively implementing environmental initiatives as a response to the demands from the retailer [41]. Environmental demands on suppliers have been raised by other authors as well, e.g., References [8,10,13,18,24,42,43]. The evaluation and auditing of suppliers, as well as visiting suppliers' sites, are important parts of a green purchasing strategy [8,10,18].…”
Section: Discussionmentioning
confidence: 99%
“…Environmental demands on suppliers have been raised by other authors as well, e.g., References [8,10,13,18,24,42,43]. The evaluation and auditing of suppliers, as well as visiting suppliers' sites, are important parts of a green purchasing strategy [8,10,18]. This is important for ensuring supplier compliance and for driving the joint work on environmental performance improvements [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence most Indian companies need to shift or modify their existing SCM to GSCM to environmental sustainability, starting with the green procurement strategies. The authors like [14] have found that the aftermath of climate change and global warming are increasing in the mind of consumers,andhence, this matter is taken seriously not only by industries and practitioners but also consumers. Enterprises are facing problems in reducing waste, CO2 emission, and utilization of energy.…”
Section: Literature Reviewmentioning
confidence: 99%
“…CO2 emission norms [14] B. Government support The government plays a significant role in the adoption of innovation as the government sets all the regulations.…”
Section: B4mentioning
confidence: 99%